CYBERNETIC MODEL OF THE ECONOMIC AGENT - STEFANESCU, Roxana (Annals of Spiru Haret University. Economic Series, 2016)
The paper is based on the synthesis of the economic systems and processes management. It analysis the cybernetic characteristics of the economy, it defines in a system manner the market and analysis its characteristic traits and synthesizes the cybernetic characteristics of the economic agent. In the first part of the paper the systemic and cybernetic traits of the market that determines the behavior and functionality of the economic systems are identified. In the second part are presented the economic agents, categorized in elementary agents and aggregate agents. At the end the economic agents are shown from the systemic, cybernetic perspective.